Implementasi Metode Sima’i Dalam Meningkatkan Kualitas Hafalan Pada Pembelajaran Tahfidz - ‘Aini, Shabahal; Praptiningsih (Universitas Majalengka, 2023)
This research aims to find out how to implement the sima'i method in improving the quality of memorization in class IX tahfidz learning at the Darul Hijroh Sukoharjo Islamic Boarding School for the 2023/2024 academic year and the factors that support and hinder the implementation of the sima'i method in improving the quality of memorization in Tahfidz learning at the Darul Hijroh Sukoharjo Islamic Boarding School for the 2023/2024 Academic Year. This research uses qualitative methods and uses data collection tools in the form of observation, interview methods and documentation. Based on the results of research that has been obtained, the Darul Hijroh Sukoharjo Islamic Boarding School in memorizing activities using the sima'i method individually is quite good because there are stages that students must go through.